Symposium on Simplicity in Algorithms (SOSA) 2022
DOI: 10.1137/1.9781611977066.3
|View full text |Cite
|
Sign up to set email alerts
|

Simpler Adjacency Labeling for Planar Graphs with B-Trees

Abstract: A permutation graph is the intersection graph of a set of segments between two parallel lines. In other words, they are defined by a permutation π on n elements, such that u and v are adjacent if an only if u < v but π(u) > π(v). We consider the problem of computing the distances in such a graph in the setting of informative labeling schemes.The goal of such a scheme is to assign a short bitstring ℓ(u) to every vertex u, such that the distance between u and v can be computed using only ℓ(u) and ℓ(v), and no fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…use of the bulk tree sequences from [12] as a "black box" in Sections 2 and 3, they can also be replaced with the approach based on B-trees from [14] in these proofs. This reduces the factor 𝑛 ⋅ 2 𝑂( √ log 𝑛⋅log log 𝑛) in Theorems 1 and 2 to 𝑛 ⋅ 2 𝑂( √ log 𝑛) .…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%
See 3 more Smart Citations
“…use of the bulk tree sequences from [12] as a "black box" in Sections 2 and 3, they can also be replaced with the approach based on B-trees from [14] in these proofs. This reduces the factor 𝑛 ⋅ 2 𝑂( √ log 𝑛⋅log log 𝑛) in Theorems 1 and 2 to 𝑛 ⋅ 2 𝑂( √ log 𝑛) .…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%
“…Very recently, Gawrychowski and Janczewski [14] showed that the use of bulk tree sequences in [12] could be replaced with a simpler approach based on B‐trees, while leaving the rest of the proof essentially unchanged. This simplifies the data‐structure part of the proof in [12] and also gives a slightly improved bound of n·2Ofalse(lognfalse)$n\cdot 2^{O(\sqrt {\log n})}$ on the number of vertices in the resulting induced‐universal graph for n$n$‐vertex planar graphs, compared to n·2Ofalse(logn·loglognfalse)$n\cdot 2^{O(\sqrt {\log n \cdot \log \log n})}$ in [12].…”
Section: Note Added In Proofmentioning
confidence: 99%
See 2 more Smart Citations